Degradation of Azo Dye, Acid Red-14 by Hexacyanoferrate(III) Using Iridium Nanoclusters: A Kinetic Study - Lasyal, Rajni; Goel, Anjali (Asian Journal of Chemistry, 2015)
In the present work, a novel method for the treatment of wastewater containing an azo dye, acid red-14 by hexacyanoferrate [HCF(III)] in presence of iridium nanoclusters has been proposed. The effect of some important operational parameters such as pH, temperature and catalyst concentration (iridium nano) has been investigated by kinetic spectrophotometric method at lmax 515 nm of the reaction mixture. The results reveal that degradation kinetics of acid red-14 follows first order kinetic model with respect to [HCF(III)], [acid red-14] and Ir nano concentration. Iridium nanoclusters were recovered with the help of centrifugation and reused for three consecutive cycles. Thermodynamic parameters Ea, DS#, DF#, DH# and ‘A’ have been calculated by studying the reaction rate in the range of temperatures 40 to 55 °C. The formation of degradation products was characterized by chromatographic and spectroscopic techniques after the extraction with ethyl acetate. 1-Hydroxy-2-amino naphthalene and naphthalene sodium sulphate were identified as major degradation products. The results can provide fundamental knowledge for the treatment of wastewater containing acid red-14/other azo dyes.